Evolution of fungal phenotypic disparity - Smith, TJ; Donoghue, PCJ (Springer Nature, 2022)
Organismal-grade multicellularity has been achieved only in animals, plants and fungi. All three kingdoms manifest phenotypically disparate body plans but their evolution has only been considered in detail for animals. Here we tested the general relevance of hypotheses on the evolutionary assembly of animal body plans by characterizing the evolution of fungal phenotypic variety (disparity). The distribution of living fungal form is defined by four distinct morphotypes: flagellated; zygomycetous; sac-bearing; and club-bearing. The discontinuity between morphotypes is a consequence of extinction, indicating that a complete record of fungal disparity would present a more homogeneous distribution of form. Fungal disparity expands episodically through time, punctuated by a sharp increase associated with the emergence of multicellular body plans. Simulations show these temporal trends to be non-random and at least partially shaped by hierarchical contingency. These trends are decoupled from changes in gene number, genome size and taxonomic diversity. Only differences in organismal complexity, characterized as the number of traits that constitute an organism, exhibit a meaningful relationship with fungal disparity. Both animals and fungi exhibit episodic increases in disparity through time, resulting in distributions of form made discontinuous by extinction. These congruences suggest a common mode of multicellular body plan evolution.